2016
DOI: 10.1111/jgs.14093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ownership on Hospice Service Use: 2005–2011

Abstract: Background/Objectives For-profit agencies comprise the majority of all United States hospice agencies, prompting concerns about aggressive enrollment practices and deficient care. Using detailed administrative data from 2005–2011, we sought to assess differences in patient populations and service use by hospice ownership, chain status, and agency size. Design/Participants Retrospective cohort study of 5,405,526 Medicare beneficiaries age 65+ enrolled in hospice during 2005–2011. Hospice use by ownership cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…The finding of the positive relationship between the prevalence of for-profit hospices and racial/ethnic minority Medicare utilization is not surprising given previous research showed for-profit hospices engage in greater community outreach to racial/ethnic minorities and low-income communities than nonprofit hospices (Aldridge et al, 2014; Stevenson et al, 2016). Prior research showed that both lower income and lower education were associated with lower rates of hospice care enrollment and at-home hospice death when holding other covariates constant (Barclay, Kuchibhatla, Tulsky, & Johnson, 2013; Jenkins et al, 2011; Silveira, Connor, Goold, McMahon, & Feudtner, 2011).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The finding of the positive relationship between the prevalence of for-profit hospices and racial/ethnic minority Medicare utilization is not surprising given previous research showed for-profit hospices engage in greater community outreach to racial/ethnic minorities and low-income communities than nonprofit hospices (Aldridge et al, 2014; Stevenson et al, 2016). Prior research showed that both lower income and lower education were associated with lower rates of hospice care enrollment and at-home hospice death when holding other covariates constant (Barclay, Kuchibhatla, Tulsky, & Johnson, 2013; Jenkins et al, 2011; Silveira, Connor, Goold, McMahon, & Feudtner, 2011).…”
Section: Discussionmentioning
confidence: 80%
“…One variable that relates to a greater number of racial/ethnic minorities receiving information about hospice is hospice ownership status. For-profit hospices tend to engage in greater community outreach to low-income and racial/ethnic minority communities than nonprofit hospices (Aldridge et al, 2014; Stevenson, Grabowski, Keating, & Huskamp, 2016). Stevenson et al (2016) found this relationship persisted despite its chain status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings substantiated previous work, suggesting that savings diminished with prolonged stay [4][5][6] and that traits and behaviors inherent to hospice agencies influenced lengths of stay. 7 The study underscored the need for providers to be proper stewards of finite healthcare resources as they continue to advocate for hospice use.…”
Section: Individualized Cost-effectiveness Analysis Of Patient-centermentioning
confidence: 99%
“…The use of hospice has expanded rapidly in recent decades, with almost 48% of Medicare decedents receiving hospice care in 2014 . Variations in delivery of hospice to individuals with different diagnoses and in different settings have led to concerns about quality of care . The Affordable Care Act required the Centers for Medicare and Medicaid Services to develop a plan to publicly report quality data for hospices using standardized measures across settings .…”
mentioning
confidence: 99%